THE EVOLUTION OF CLASSICAL POLITICAL PHILOSOPHY: FROM PLATO TO MACHIAVELLI - Verma, Durgesh (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Examining the evolution of classical political theories with respect to the contributions made by eminent political philosophers from Plato to Machiavelli, this study emphasising the importance of pragmatic administration, virtue, and constitutional government, contrasts Aristotle’s political realism with Plato’s idealism focused in the idea of philosopher-king and his vision of a desirable society. The study then moves to the Middle Ages, underlining the impact of St. Augustine’s Christian political philosophy, which offered a dualistic perspective of heavenly and earthly government, therefore affecting the interaction between church and state. At last, the research revolves on Niccolò Machiavelli, who broke with the moralistic approaches of his contemporaries to advocate political pragmatism and realism. Machiavelli’s ideas on power, leadership, and the division of ethics from politics in The Prince and Discourses on Livy placed modern political realism starting with statecraft and survival above idealistic elements. By means of a comparison of these thinkers, the research reveals how the idealistic notions of Plato gave way to Machiavelli’s pragmatic approach whereby power and adaptability were vital for political success. The study also examines the different ways during these centuries power, morality, and authority influenced political systems. The study underlines how still today classical political philosophy shapes contemporary political institutions and methods. It finishes with highlighting the continuous relevance of these ideas in contemporary political discourse and provides suggestions for next study on the evolving character of political philosophy. This analogy highlights the basic contributions made by every thinker as well as the procedures guiding the foundation of present political philosophy.